2019
DOI: 10.1186/s13068-019-1489-5
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of 3-hydroxypropanoate metabolism in Cupriavidus necator H16

Abstract: Background: 3-Hydroxypropionic acid (3-HP) is a promising platform chemical with various industrial applications. Several metabolic routes to produce 3-HP from organic substrates such as sugars or glycerol have been implemented in yeast, enterobacterial species and other microorganisms. In this study, the native 3-HP metabolism of Cupriavidus necator was investigated and manipulated as it represents a promising chassis for the production of 3-HP and other fatty acid derivatives from CO 2 and H 2. Results: When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
(90 reference statements)
0
15
0
Order By: Relevance
“…During shake-flask cultivation the methylmalonate-semialdehyde dehydrogenase (g153; Ap ald6 ) is strongly up-regulated at all times in the engineered strains. This enzyme, normally involved in branched-chain amino acid degradation, has been implicated in 3HP metabolism in bacteria ( Zhou et al, 2014 ; Arenas-Lopez et al, 2019 ) and the yeast C. albicans ( Otzen et al, 2014 ) by also acting as a malonate-semialdehyde dehydrogenase and diverting flux toward acetyl-CoA rather than 3HP. Here we deleted a putative malonate-semialdehyde dehydrogenase Ap ald6 and found that 3HP yield was drastically improved ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…During shake-flask cultivation the methylmalonate-semialdehyde dehydrogenase (g153; Ap ald6 ) is strongly up-regulated at all times in the engineered strains. This enzyme, normally involved in branched-chain amino acid degradation, has been implicated in 3HP metabolism in bacteria ( Zhou et al, 2014 ; Arenas-Lopez et al, 2019 ) and the yeast C. albicans ( Otzen et al, 2014 ) by also acting as a malonate-semialdehyde dehydrogenase and diverting flux toward acetyl-CoA rather than 3HP. Here we deleted a putative malonate-semialdehyde dehydrogenase Ap ald6 and found that 3HP yield was drastically improved ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…necator H16 competent cells and for the TraDIS experiment. Chemically defined minimal medium (MM) [ 68 ] was supplemented with 4 g/l of either D-fructose (FMM), when used to grow the C . necator H16 transposon mutant library for TraDIS, or sodium D-gluconate (SGMM), when used to select C .…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, this degradation only occurs at room temperature and not at 37 • C, probably due to the inadequate ability to remove toxic malonic semialdehyde at higher temperatures (Loh et al, 2006;Kim et al, 2010). Currently, we do not know if Rmet_1009, similar to RutE, reduces malonic semialdehyde to 3-hydroxypropionic acid and if C. metallidurans CH34 carries other genes that encode for proteins that enable the removal of malonic semialdehyde, similar to Cupriavidus necator H16 (Arenas-López et al, 2019). Nevertheless, our results point toward metabolic poisoning of C. metallidurans grown in high-concentration nitrogencontaining media at 37 • C.…”
Section: Discussionmentioning
confidence: 99%